PENGARUH MOTIVASI, PENDIDIKAN, PELATIHAN DAN KONDISI KERJA TERHADAP KINERJA PEGAWAI UNIVERSITAS MUHAMMADIYAH PALU - Pariyati, Pariyati (Katalogis, 2013)
This purpose of this research was to find out how big the contribution of variable motivation, education, training, and work condition and to find out the effect of each variable toward the performance of staff of Muhammadiyah University, Palu. To analyse the data, double linear regression with SPSS 16,0 (Statistical Program for Social Science) was employed. The number of respondent was 135 persons. The result of test showed that the variable of motivation, education, training and work condition, partially, had significant effect toward the performance as indicated the value of probability < 0,05. The effect of motivation, education, training and work condition toward the performance of staff contributed to F-Counted of 5,001 with the degree of probability 0,000 (significant) which meant that motivation, education, training and work condition, stimultanously, had significant effect toward the performance of staff of Muhammadiyah University, Palu.